Lactobacillus rhamnosus GR-1 Prevents Escherichia coli-Induced Apoptosis Through PINK1/Parkin-Mediated Mitophagy in Bovine Mastitis - Li, Yanan; Zhu, Yaohong; Chu, Bingxin; Liu, Ning; Chen, Shiyan; Wang, Jiufeng (Frontiers in Immunology, 2021)
Escherichia coli is one of the most important pathogens that cause clinical mastitis in dairy cattle worldwide and lead to severe economic losses. Antibiotics are often used to treat this inflammatory disease; however, antimicrobial resistance and environmental pollution cannot be ignored. Probiotic is the best alternative; however, its mechanisms of action to prevent mastitis remain unclear. Moreover, the role of probiotics in regulating mitophagy, a selective autophagy that maintains mitochondrial quality, needs to be explored. E. coli infection induced NOD-like receptor family member pyrin domain-containing protein 3 (NLRP3) inflammasome assembly, Caspase-1 activation, and apoptosis in MAC-T cells. Infection also resulted in mitochondrial damage and subsequent increase in reactive oxygen species (ROS) production. Moreover, inhibition of ROS release by scavenger N-acetyl-L-cysteine (NAC) abrogated the importance of ROS in NLRP3 assembly and apoptosis in MAC-T cells. Pretreatment with Lactobacillus rhamnosus GR-1 (LGR-1), a probiotic, alleviated E. coli-induced NLRP3 inflammasome activation and apoptosis via ROS inhibition. Besides, E. coli infection inhibited mitophagy while LGR-1 pretreatment augmented PINK1/Parkin–mediated mitophagy activation, which further blocked ROS generation. To explore the effect of LGR-1 in vivo, a mouse mastitis model was established. The results showed that LGR-1 pretreatment had preventive and protective effects on E. coli induced mastitis, and could reduce cytokines levels such as IL-1β and TNF- α. In accordance with the results in vitro, E. coli can inhibit mitophagy and activate NLRP3 inflammasome and apoptosis, while LGR-1 can weaken the effect of E. coli. Taken together, our data indicated that LGR-1 pretreatment induced PINK1/Parkin-mediated mitophagy that eliminated damaged mitochondria and reduced ROS production and NLRP3 inflammasome activation, which subsequently decreased E. coli-induced apoptosis. To conclude, our study suggests that therapeutic strategies aiming at the upregulation of mitophagy under E. coli-induced mastitis may preserve mitochondrial function and provide theoretical support for the application of probiotics in bovine mastitis.